Molecular Mechanism of SAHA on Regulation of Autophagic Cell Death in Tamoxifen-Resistant MCF-7 Breast Cancer Cells - Young Ju Lee, A Jin Won, Jaewon Lee, Jee H. Jung, Sungpil Yoon, Byung Mu Lee, Hyung Sik Kim (International Journal of Medical Sciences, 2012)
Objective: Tamoxifen is currently used for the treatment of estrogen receptor-positive breast cancer patients, but acquired resistance to tamoxifen is a critical problem in breast cancer therapy. Suberoylanilide hydroxamic acid (SAHA) is a prototype of the newly developed HDAC inhibitor. The aim of this study is to investigate the anticancer effects of SAHA in tamoxifen-resistant MCF-7 (TAMR/MCF-7) cells. Methods: Cytotoxicity, apoptosis and autophagic cell death induced by SAHA were studied. A TAMR/MCF-7 cells xenograft model was established to investigate the inhibitory effect of SAHA on tumor growth in vivo. Results: SAHA inhibited the proliferation of TAMR/MCF-7 cells in a dose-dependent manner. SAHA significantly reduced the expression of HDAC1, 2, 3, 4 and 7 and increased acetylated histone H3 and H4. Although SAHA induced G2/M phase arrest of cell cycle, apoptotic cell death was very low, which is correlated with the slight change in the activation of caspases and PARP cleavage. Interestingly, expression of the autophagic cell death markers, LC3-II and beclin-1, was significantly increased in TAMR/MCF-7 cells treated with SAHA. Autophagic cell death induced by SAHA was confirmed by acridine orange staining and transmission electron microscopy (TEM) in TAMR/MCF-7 cells. In mice bearing the TAMR/MCF-7 cell xenografts, SAHA significantly reduced the tumor growth and weight, without apparent side effects. Conclusion: These results suggest that SAHA can induce caspase-independent autophagic cell death rather than apoptotic cell death in TAMR/MCF-7 cells. SAHA-mediated autophagic cell death is a promising new strategy to treatment of tamoxifen-resistant human breast cancer.